The Effect of Group Investigation Model and Learning Style on Students’ Writing of Descriptive Text - Maesaroh, Maesaroh (Journal of English Education Studies, 2021)
This research objectives are to analyze the students cooperative learning group Investigation model and three-phase technique; To analyze the visual students and auditory students; To analyze the interaction between group investigation model and students learning styles. This is a true-experimental research. The sample selection was done by random class technique as much as two classes, where the first class was taught by group investigation model and second class with three-phase technique. The instruments used are validated conceptual test and questionnaires. The data in this research were analyzed using two-way ANOVA. The results showed that the students using cooperative learning group investigation model was better than three-phase technique. Visual students shows better results than auditory students. There is an interaction between group Investigation model and students learning styles. This interaction shows visual students is dominant in group investigation model.